Azo-dye orange II degradation by the heterogeneous Fenton-like process using a zeolite Y-Fe catalyst-Kinetics with a model based on the Fermi's equation - Maryin L. Rache (2014)
The degradation of Orange II dye (OII) by a heterogeneous Fenton-like process was studied using a catalyst with 5 wt.% of iron after ion-exchange in a Na-Y zeolite support. The catalyst was characterized by X-ray diffraction (XRD), N-2 adsorption, atomic absorption spectroscopy and X-ray fluorescence (XRF). The effect of the initial concentrations of H2O2 and OH, pH and temperature on the degradation rate of OH was investigated by carrying out experiments in a batch reactor. The OII concentration histories (i.e., concentration evolution along reaction time) were described by a simple semi-empirical kinetic model, based on the Fermi's equation, which captures simultaneously the influence of all the reaction conditions with a few adjustable parameters. The adherence of the model to the data was remarkable, and the effect of the operating conditions on the obtained fitting parameters - apparent rate constant and transition time - was analyzed.